1990
DOI: 10.1007/bf02821279
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of biosynthesis of thiolutin and aureothricin inStreptomyces kasugaensis

Abstract: L-Methionine and DL-ethionine decreased production of thiolutin and aureothricin in Streptomyces kasugaensis. In the presence of L-methionine the culture also produced 3-methylthioacrylic acid, 3-methylthiopropionic acid and 3,6-bis-(2-methylthioethyl)-2,5-dioxopiperazine. Production of the metabolites depended on the concentration of L-methionine in the medium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…The later amino acids supported the growth rate but not antibiotic productions. These coincide with Šturdíková et al (1990) which reported that the effect of methionine and ethionine on thiolutin and aureothricin productions by S. kasugaensis showed the same inhibitory effects. Many authors observed the negative effect of methionine on secondary metabolites biosynthesis such as ochratoxin A (Lisker and Paster 1983).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The later amino acids supported the growth rate but not antibiotic productions. These coincide with Šturdíková et al (1990) which reported that the effect of methionine and ethionine on thiolutin and aureothricin productions by S. kasugaensis showed the same inhibitory effects. Many authors observed the negative effect of methionine on secondary metabolites biosynthesis such as ochratoxin A (Lisker and Paster 1983).…”
Section: Discussionsupporting
confidence: 89%
“…We found that the addition of 10 mmol l −1 cysteine or cystine exhibited a negative effect on thiolutin production. Šturdíková et al (1990) conducted a similar study on thiolutin and aureothricin productions using S. kasugaensis . They showed that the addition of cysteine to the culture medium at 0·1% (equivalent of 8·25 mmol l −1 ) did not affect the yield of thiolutin and aureothricin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This www.elsevier.com/locate/procbio Process Biochemistry 42 (2007) [925][926][927][928][929][930][931][932][933] class of antibiotics exhibits protozoicidal, larvicidal and insecticidal activities [5,7,8]. Dithiolopyrrolones have also been reported to have anticancer activity [9].…”
Section: Introductionmentioning
confidence: 99%
“…The dithiolopyrrolones are effective against various microorganisms including Gram-positive and -negative bacteria, yeasts, filamentous fungi and ameboid parasites [5,7]. This www.elsevier.com/locate/procbio Process Biochemistry 42 (2007) [925][926][927][928][929][930][931][932][933] class of antibiotics exhibits protozoicidal, larvicidal and insecticidal activities [5,7,8].…”
Section: Introductionmentioning
confidence: 99%